0148 Using the UK Biobank study to estimate occupational causes of chronic disease: comparability with the UK national population and adjustment for bias. (23rd June 2014) - Hutchings, Sally; Ayres, Jon; Cullinan, Paul; Fishwick, David; Jarvis, Debbie; De Matteis, Sara; Sadhra, Steve; Wheatley, Magda; Rushton, Lesley
Abstract : Objectives: The UK Biobank study is a sample of 502, 682 people aged 40–70, clustered around 22 assessment centres. As part of a project to investigate the causes of COPD and estimate the UK occupational burden, we have assessed the sample's representativeness with respect to the UK national population, with a view to accounting for potential biases. Method: We have compared characteristics of the Biobank population (age, education, employment, smoking etc) to that of the UK population as estimated from national data sources. Results: Deprivation index scores indicate that Biobank respondents in more affluent wards are over-represented (52% of Biobank respondents versus 28% nationally have scores of less than -2). The Biobank respondents are also better-educated (33% to degree level, 17% nationally), with similar qualification levels in men and women, whereas more men than women nationally in this age range had higher level qualifications. Fewer were currently employed than nationally (58% vs. 65%), particularly men over 60, with more retired (45% vs. 33%), and fewer disabled or unemployed. There are more in managerial and professional (54% vs. 46%), and fewer in routine and manual occupations (22%, 33% nationally), and fewer smokers (33% vs. 49%). Fewer in the already under-represented unskilled occupations (47% vs. 70% for other occupations), or with reported respiratory ill-health (50% vs. 59%) have a usable email address. Conclusions: As Biobank respondents are on average less deprived, better educated and under-represented in unskilled occupations than the national population, estimating national occupational COPD burden, and collecting further data without bias will require data adjustments.